Seeing past the tip of your own nose? How outward and self-centred orientations could contribute to closing the green gap despite helplessness - Adamus, Magdalena; Šrol, Jakub; Čavojová, Vladimíra; Ballová Mikušková, Eva (BMC psychology, 2023)
BACKGROUND: The present study explored moderators of the relation between environmental concerns and pro-environmental behaviour that could help close the green gap. METHODS: A sample of 500 individuals (250 women) participated in the study. Apart from socio-demographic characteristics, participants answered questions about their environmental concerns and pro-environmental behaviour, collectivism and individualism, time orientation and emotional responses to climate change. RESULTS: Our results corroborate the view that collectivism, future orientation and prosocial tendencies may form a single component of outward orientation, while individualism and immediate orientation form self-centred orientation. Generally, outwardly oriented individuals and those less self-centred reported more pro-environmental behaviour. However, strongly self-centred individuals, even when reporting elevated helplessness, showed increased involvement in pro-environmental behaviour once their concerns were high. CONCLUSIONS: The study contributes to the literature by pointing out that both outward and self-centred orientations have the potential to insulate individuals against the negative effect helplessness may have on pro-environmental behaviour. This could inform strategies that would both prompt individuals already concerned to act and arouse more concern among those who are not yet preoccupied with climate change.
Keywords: Environmental concern; emoce; Prosocial tendencies; individualita; Emotions; Collectivism-individualism; lidé; Female; Social Behavior; Helplessness; Future orientation; Individuality; Pro-environmental behaviour; sociální chování; Green gap; ženské pohlaví; Humans